Peningkatan Pati Resisten Tepung Sorgum Termodifikasi Melalui Fermentasi dan Siklus Pemanasan Bertekanan-Pendinginan - Raden Haryo Bimo Setiarto; Nunuk Widhyastuti; Denny Setiadi (Jurnal Ilmu Pertanian Indonesia, 2018)
Sorghum can be utilized as raw material to produce resistant starch because of its high amylose content. Resistant starch is the starch that is resistant to gastric acid hydrolysis and it cannot be digested by pancreatic digestive enzymes, it cannot be absorbed in the human small intestine, but it can be fermented by intestinal microbial in the colon. This study aims to increase the levels of resistant starch in modified sorghum flour by lactic acid bacteria fermentation and autoclaving-cooling cycling. Parameters analyzed in this study were proximate analysis starch digestibility, amylose content, total starch, reducing sugar, RDS (rapidly digestible starch), SDS (slowly digestible starch), and resistant starch. The combination treatment of fermentation and 2 cycles of autoclaving-cooling (FAC-2S) is the best treatment because it was able to produce the highest resistant starch content (39.06% dw) and it increased resistant starch 8.1 fold when compared with control. Improvement the number of autoclaving-cooling cycles was applied will increase the resistant starch content and decrease the digestibility of modified sorghum flour. High amylose content in modified sorghum flour is useful in the formation of resistant starch.